Childhood Exposure to Low to Moderate Doses of Ionizing Radiation and the Risk of Vascular Diseases: The Tinea Capitis Study. Issue 3 (30th September 2020) - Sadetzki, Siegal; Chetrit, Angela; Boursi, Ben; Luxenburg, Osnat; Novikov, Ilya; Cohen, Arnon
Abstract: In the Tinea Capitis Study (Israel, 1966–2011), we assessed the association between childhood exposure to low to moderate doses of ionizing radiation (IR) to the head and neck and the development of vascular diseases (ischemic heart disease, carotid artery stenosis, and stroke) in adulthood. The study included 17, 734 individuals from the Tinea Capitis cohort (7, 408 irradiated in childhood and 10, 326 nonirradiated), insured by Israel's largest health provider. Individual dosimetry was estimated based on measurements made on a head phantom and original treatment records. The mean doses were 1.5, 0.09, 0.78, and 0.017 Gy to brain, thyroid, salivary gland, and breast, respectively. Data on vascular diseases was abstracted from computerized medical records. Using Poisson regressions, we examined the association of radiation with morbidity. Any vascular disease was reported for 2, 221 individuals. Adjusted for age, sex, socioeconomic status, smoking, hypertension, and diabetes, exposure to IR increased the risk of developing any vascular diseases (relative risk (RR) = 1.19, 95% confidence interval (CI): 1.09, 1.29), stroke (RR = 1.35, 1.20, 1.53), carotid artery stenosis (RR = 1.32, 1.06, 1.64), and ischemic heart disease (RR = 1.12, 1.01, 1.26). The risk of developing vascular diseases was positively associated with dose and inversely associated with age at exposure. In conclusion, the results indicate that early exposure to low to moderate doses of IR increases the risk of cerebro- and cardiovascular impairments.